Human perturbation increases the fluxes of dissolved molybdenum from land to ocean — The case of the Jiulong River in China. (15th March 2018) - Wang, Deli; Lu, Shuimiao; Chen, Nengwang; Dai, Minhan; Guéguen, Céline
Abstract: Rivers contribute a substantial amount of trace metals including molybdenum (Mo) into the oceans. The driving forces controlling the riverine fluxes of dissolved metals still remain not fully understood. Our study then investigated the spatial variations of dissolved metals including molybdenum in a typically human perturbed river, the Jiulong River (JR), China. The aim of the study is to elucidate the relevance of anthropogenic perturbation on the fluxes of dissolved metals such as molybdenum from land to ocean. Our study shows a large spatial variability of dissolved Mo across tributary to main stream of the JR. Particularly, dissolved Mo was generally low (average: 5 ± 1 nM) in the "pristine" JR headwaters, and elevated (19 ± 6 nM) along the lower river continuum. Sporadically high levels of dissolved Mo occurred in the upper North River (77 ± 19 nM), as a result of mining activities locally. Significant correlations of dissolved Mo with total dissolved solids (TDS) and dissolved strontium (Sr) were observed in the whole JR (Mo = 1.4* TDS -1.7, R 2 = 0.86, p < .01; Mo = 1.2*Sr – 2.2, R 2 = 0.70, p < .01, logarithmic scales). This indicates that dissolved Mo is mobilized mainly along with other major ions such as Sr during similar mineral dissolution processes. From the "pristine" headwaters to the mouth of the JR, riverine Mo fluxes at the mouth of the JR has elevated by at least 3 times due to human perturbation. Compiled historic data regarding metal fluxes from world rivers further confirmed that small and medium rivers are relatively more sensitive to human perturbation. Highlights: Dissolved molybdenum is quite variable from tributary to stream of a river. Molybdenum in minerals experiences weathering processes similar to major ions. Human perturbation drives the cycling of dissolved constituents like molybdenum in rivers.